Pemanfaatan Google App Script (GAS) untuk Mempermudah Pengumpulan Dokumen pada Google Forms - Tedi Purwanto (CV. Multi Kreasi Media, 2026)
Document collection through Google Forms by default stores uploaded files in a fragmented structure, making data management difficult, especially when involving many respondents with multiple documents. This research aims to optimize the document collection and management process on Google Forms by utilizing Google Apps Script (GAS). The method used is the development of an automatic script capable of grouping documents based on users by creating individual folders named according to each respondent's email. The research results show that GAS implementation can significantly facilitate file organization in large quantities and many users. This system also enables the addition of status tracking on Google Sheets for more effective monitoring. Thus, the utilization of GAS has proven to provide a practical solution in overcoming the limitations of Google Forms' default features, particularly in terms of more structured and efficient document management and organization.